Structural design and optimization of egg carrier for dynamic egg slit detection platforms - Ronghua Meng; Yuxiang Tian; Siwei Huang (PLoS ONE, 2025)
This paper presents an improved egg carrier for supporting common types of eggs during an egg slit inspection platform opeations. The carrier conveys the eggs forwards to the inspection position. The egg carrier consists of three basic modules and has the advantages of adaptability, adjustability, low maintenance and manufacturing costs, and stable and efficient operation. First, the egg carrier functions are analysed, and preliminary design concepts and solutions are proposed via TRIZ theory. Second, the egg carrier structure is designed, the material properties are analysed, and key parameters such as deformation are simulated by SolidWorks and Ansys Workbench. Finite element and fatigue analyses are carried out for the key parameters of the structure, and deformation, fatigue and other data that appear in the actual operation process are obtained. On the basis of stable egg carrying, a carrying motion mathematical model is established, and the genetic algorithm (GA) is chosen to optimize the structural parameters. Finally, motion simulation is carried out for the improved egg carrier, which verifies the optimized structure reasonableness.